Top-Ten Tips for Imaging Groin Injury in Athletes - Madani, Hardi; Robinson, Philip (Seminars in Musculoskeletal Radiology, 2019)
Athletic groin injury remains a challenging prospect for sports clinicians and radiologists because of the closely related anatomical structures and overlapping clinical presentations. Recent consensus work designated four causative clinical entities, with the adductor/rectus aponeurosis and pubic symphysis capsule emphasized as key areas. This article highlights these key aspects of athletic groin injury with tips on anatomy, potential abnormalities, acronyms, and imaging appearances in this complex but common and potentially incapacitating entity. Many clinical and radiologic terms are in use such as cleft, enthesitis, plate injury, or defect that can cause confusion, and thus anatomical descriptions are preferable.Detailed clinical assessment is necessary but remains challenging because of the nonspecific presentations. Imaging, and in particular magnetic resonance imaging, plays an essential role in the evaluation process. But only when the two are used in combination can an accurate diagnosis be reached because several studies in asymptomatic athletes show that reactive changes are common.
Keywords: athletic groin pain; symphysis pubis; MRI; ultrasound; muscle injury